THE IMPACT OF MOBILE PHONE IN LEARNING - Jakhongir Buriboev; Yuldosheva Kamola (Ta’lim innovatsiyasi va integratsiyasi, 2025)
This study delves into the influence of mobile phones on classroom learning. Mobile phones, enabling learning anytime and anywhere, have enhanced communication and boosted student motivation, making them valuable tools in education. However, challenges such as distraction and academic misconduct have emerged. To mitigate these issues, school administrators actively monitor mobile phone usage in classrooms. This article examines key principles and challenges related to the integration of mobile phones into lessons. It also offers personal insights on effectively incorporating these devices. The primary aim of this research is to analyze how educators and leaders address the duality of mobile technology in education. While digital natives exhibit strong positive attitudes towards technology and possess basic technical skills, they often lack proficiency in advanced, classroom-specific applications. As educators increasingly explore the integration of mobile phones in teaching, they evaluate both the opportunities and obstacles associated with this technology.